Ego-resiliency and Tinnitus Annoyance - Fludra, Małgorzata; Kobosko, Joanna; Gos, Elżbieta; Paluchowska, Justyna; Skarżyński, Henryk (Journal of the American Academy of Audiology, 2022)
Background Tinnitus is a common and, in many cases, chronic condition. Coping with a chronic ailment is a long-term process, which also depends on the personality of the individual. One important personality resource is ego-resiliency, that is, how flexible the person is in adapting to the impulse to control their environment.Purpose The aim of the study was to determine whether ego-resiliency affects the perceived level of tinnitus annoyance.Research Design This was a questionnaire study combined with a retrospective analysis of medical data.Study Sample The study involved 176 people with diagnosed chronic tinnitus who volunteered to participate (53 men and 123 women aged 31–80 years).Data Collection and Analysis The following tools were used: Ego-Resiliency Scale to measure ego-resiliency, Tinnitus Functional Index to assess the impact of tinnitus on daily life, and a survey of sociodemographics and tinnitus history.Results The conducted research showed that men had higher ego-resiliency than women. Older subjects (older than 60 years) had higher ego-resiliency than younger ones. There was a negative correlation between ego-resiliency and the perceived annoyance of tinnitus. Regression analysis showed that a person's ability to cope and to tolerate negative emotions were the only factors of ego-resiliency that were a significant predictor of tinnitus annoyance.Conclusion People with a high level of personal ability to cope and to tolerate negative emotions are likely to experience decreased tinnitus annoyance. Ego-resiliency levels should be considered when diagnosing and planning interventions for people with tinnitus. In psychological intervention programs for people with tinnitus, it is worthwhile developing ego-resiliency, paying particular attention to positive emotions which are crucial in building it. Research should be continued on other personal resources affecting perceived tinnitus annoyance.
Keywords: ego-resiliency; tinnitus; personal resources; psychological intervention